2017
DOI: 10.3389/fpls.2017.00600
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Alleviates the Adverse Effects of Salt Stress on Dianthus superbus (Caryophyllaceae) by Activating Photosynthesis, Protecting Morphological Structure, and Enhancing the Antioxidant System

Abstract: Salt stress critically affects the physiological processes and morphological structure of plants, resulting in reduced plant growth. Salicylic acid (SA) is an important signal molecule that mitigates the adverse effects of salt stress on plants. Large pink Dianthus superbus L. (Caryophyllaceae) usually exhibit salt-tolerant traits under natural conditions. To further clarify the salt-tolerance level of D. superbus and the regulating mechanism of exogenous SA on the growth of D. superbus under different salt st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
95
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(112 citation statements)
references
References 55 publications
16
95
1
Order By: Relevance
“…Most studies have suggested that SA application inhibits CAT activity (Klessig et al , Larkindale and Huang ). Despite these works, similar to findings in the Özen roots in the present study, increases in CAT activity with the application of SA were recorded in grass pea under drought, (Xiong et al ) and Dianthus superbus under salt stress (Ma et al ). The accumulation of H 2 O 2 observed in the SA‐treated Tarm roots could be the result of the inhibition of CAT activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most studies have suggested that SA application inhibits CAT activity (Klessig et al , Larkindale and Huang ). Despite these works, similar to findings in the Özen roots in the present study, increases in CAT activity with the application of SA were recorded in grass pea under drought, (Xiong et al ) and Dianthus superbus under salt stress (Ma et al ). The accumulation of H 2 O 2 observed in the SA‐treated Tarm roots could be the result of the inhibition of CAT activity.…”
Section: Discussionsupporting
confidence: 89%
“…in Glycine max (Gutiérrez-Coronado et al 1998), Triticum aestivum (Shakirova et al 2003), Zea mays (Gunes et al 2007), Matricaria chamomilla (Kovácik et al 2009), Arabidopsis thaliana (Jayakannan et al 2013) and Vigna radiata (Khan et al 2014). In addition, antioxidant responses have also been investigated for salt stress alone in Torreya grandis (Li et al 2014), Vicia faba (Azooz 2009), Oryza sativa (Jini and Joseph 2017) and Dianthus superbus (Ma et al 2017). Moreover, by regulating the antioxidant defense system, SA application was shown to alleviate adverse effects in drought-stressed A. thaliana (Miura et al 2013) and T. aestivum (Sedaghat et al 2017) and heat-stressed Z. mays (Horváth et al 2002), A. thaliana (Larkindale and Knight 2002), Poa pratensis (He et al 2005) and Cucumis sativa (Shi et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, an improvement in salinity tolerance is achieved with the application of salicylic acid, a molecule implicated in plant signaling defense that also helps coping with salinity [94,95]. Several mechanisms operate to enhance plant growth under salt stress after the application of salicylic acid, among them is decreasing K + efflux and H + influx from the mature root zone that occurs in response to NaCl and activating the expression of salt tolerance genes under moderate, but not under severe, salt stress [96,97]. On the other hand, salinity interferes with P translocation.…”
Section: Nutrient Managementmentioning
confidence: 99%
“…In addition, plants may respond to stress by adjusting stomatal density, aperture and spatial distribution patterns (Casson & Gray, ; Korn, ; Munns & Tester, ; M. Xu, ). For example, the stomatal density and aperture of Dianthus chinensis are reduced to cope with salt stress (X. Ma, Zheng, Zhang, Hu, & Qian, ).…”
Section: The Place Where Photosynthesis Occurs—chloroplastmentioning
confidence: 99%